2015
DOI: 10.1111/1755-5922.12144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Galanin Receptor Antagonist M40 on Cardiac Function and Remodeling in Rats with Heart Failure

Abstract: SUMMARYBackground: Sympathetic activation and parasympathetic withdrawal are important characteristics of heart failure. Recent studies demonstrate that galanin reduces the discharge of acetylcholine and inhibits vagal bradycardia by acting on galanin receptor type 1 (GalR1). We speculated that blocking GalR1 is beneficial for heart failure. Methods: Rats with heart failure were induced by myocardial infarction. The rats were injected intraperitoneally with galanin receptor antagonist M40 solution (30 nmol/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Galanin is involved in central cardiovascular regulation, which affects the blood pressure and the heart rate [2]. Administration of galanin into the rostral ventrolateral medulla produces a weak hypotension and tachycardia effect by reducing the sympathetic vasomotor tone in rats [3], which may be blocked by the intracerebroventricular injection of galanin antagonist M40 [4]. Recent studies suggest that galanin and its fragment play a major role in the regulation of metabolic homeostasis in cardiac muscle and galanin is an important hormone relative to diabetic heart [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galanin is involved in central cardiovascular regulation, which affects the blood pressure and the heart rate [2]. Administration of galanin into the rostral ventrolateral medulla produces a weak hypotension and tachycardia effect by reducing the sympathetic vasomotor tone in rats [3], which may be blocked by the intracerebroventricular injection of galanin antagonist M40 [4]. Recent studies suggest that galanin and its fragment play a major role in the regulation of metabolic homeostasis in cardiac muscle and galanin is an important hormone relative to diabetic heart [4].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of galanin into the rostral ventrolateral medulla produces a weak hypotension and tachycardia effect by reducing the sympathetic vasomotor tone in rats [3], which may be blocked by the intracerebroventricular injection of galanin antagonist M40 [4]. Recent studies suggest that galanin and its fragment play a major role in the regulation of metabolic homeostasis in cardiac muscle and galanin is an important hormone relative to diabetic heart [4]. The endogenous galanin, acting through its central receptor, has an important attribute to glucose transporter 4 (GLUT4) regulation, leading to enhanced insulin sensitivity and glucose uptake in cardiac muscle of type 2 diabetic rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…In myocytes, galanin improved contractile performance of papillary muscles following simulated ischemia reperfusion. However, induction of MI in rats treated with the GalR antagonist M40 (30 nmol/kg IP, for four weeks), showed that M40 imparted small improvements in ejection fraction and a slightly reduced LV chamber dimension compared with MI controls, resulting in a slightly reduced heart weight to body weight ratio [199]. This was accompanied by small reductions in BNP and IL-6, but not TNF-α.…”
Section: 0 Additional Neuropeptidesmentioning
confidence: 99%
“…The experimental model of heart failure was induced by ligation of the left anterior descending coronary artery (LAD) as previously described. 17) Briefly, rats were anaesthetized with 3% pentobarbital sodium (30 mg/kg, ip) and intubated for mechanical ventilation (SAR-830, CWE Inc., USA). A left thoracotomy was performed and then the LAD was exposed and ligated with a 6-0 silk suture after the pericardium was cut.…”
Section: H Eart Failure (Hf) Is a Clinical Syndrome Characterizedmentioning
confidence: 99%